Retinal pigment epithelial cells phagocytosis of T lymphocytes: possible implication in the immune privilege of the eye. Issue 12 (1st December 2002) - Willermain, F; Caspers-Velu, L; Nowak, B; Stordeur, P; Mosselmans, R; Salmon, I; Velu, T; Bruyns, C
Abstract : Aim: To investigate the capability of retinal pigment epithelium (RPE) cells to phagocytose T lymphocytes and to further analyse the immunobiological consequences of this phagocytosis. Methods: Human RPE cells pretreated or not by cytochalasin, a phagocytosis inhibitor, were co-cultured with T lymphocytes for different time points. Phagocytosis was investigated by optic microscopy, electron microscopy, and flow cytometry. T cell proliferation was measured by 3 H thymidine incorporation. RPE interleukin 1β mRNA expression was quantified by real time PCR. Results: RPE cells phagocytose apoptotic and non-apoptotic T lymphocytes, in a time dependent manner. This is an active process mediated through actin polymerisation, blocked by cytochalasin E treatment. Inhibition of RPE cell phagocytosis capabilities within RPE-T cell co-cultures led to an increase of lectin induced T cell proliferation and an upregulation of interleukin 1β mRNA expression in RPE cells. Conclusions: It is postulated that T lymphocyte phagocytosis by RPE cells might, by decreasing the total number of T lymphocytes, removing apoptotic lymphocytes, and downregulating the expression of IL-1β, participate in vivo in the induction and maintenance of the immune privilege of the eye, preventing the development of intraocular inflammation.